Science between and against disciplines in the social sciences and humanities (Journal of Education Culture and Society, 2020)
The article describes the role of interdisciplinarity in the process of making science.  Two patterns of research and development of discipline are presented: the closed pattern which concentrates  on specialization and the open pattern  which fosters interdisciplinary science. The key to success is always openness for new scientific experiences and communities. The conclusion of the article is a proposal for  finding new scientific communities, which could be interested in new ideas, research  and thoughts where interdisciplinary analyses are not acceptable to the local scientific community.